Pemberdayaan Remaja Mengatasi Tiga Ancaman Utama Kesehatan Reproduksi (Triad KKR) di Desa Bangun Rejo, Tanjung Morawa, Deli Serdang, Tahun 2025 - Mesrida Simarmata; Srininta Srininta; Elvina Panjaitan; Yohana Yakin Harefa; Dhea Puspita Winanda; , Feby Agelia; Yarni Yarni (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The Three Threats to Reproductive Health (KRR Triad) refer to serious issues that can endanger adolescent reproductive health: sexually transmitted infections (STIs), HIV/AIDS, and drug abuse. These threats often lead to harmful consequences such as reproductive diseases, unintended pregnancies, abortion, and drug addiction. The root causes include insufficient knowledge among adolescents and negative attitudes toward prevention efforts. This Community Service initiative, titled Empowerment of Adolescents with Behavior Toward the Three Basic Threats to Reproductive Health (KRR Triad), was conducted in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, in 2025. The program aimed to increase adolescents’ understanding of the KRR Triad, including its definitions, categories, impacts, and prevention strategies, while also fostering a proactive attitude among youth in addressing these threats. The participants were adolescents residing in Bangun Rejo Village. The activities were conducted from March to May 2025. The method involved a lecture-based educational session, accompanied by a pre-test and post-test to measure the participants’ knowledge and understanding. Prior to the intervention, 46.6% (14 participants) demonstrated poor knowledge regarding the KRR Triad. After the educational sessions, knowledge significantly improved, with 56.6% (17 participants) showing increased understanding. These findings indicate that structured education on reproductive health threats can effectively enhance adolescents' knowledge and potentially influence their behavior toward healthier choices. In conclusion, the community service program successfully empowered adolescents in Bangun Rejo Village with essential knowledge and awareness regarding the KRR Triad, underlining the importance of continuous reproductive health education to mitigate the risk of future health problems among youth